KUALITAS KEPUASAN PENGHUNI RUMAH SUSUN PERUM PERUMNAS PALEMBANG - Dafrimon Dafrimon (Politeknik Negeri Sriwijaya, 2012)
The solution provided by the government to meet the residence habitable for residents on low incomes are flat, so that in the long term the government can concentrate on a simple home-based apartment rental (Rusunawa). in serving the needs of the people there are limitations that are still encountered.The aim of this study is determine the level of occupant satisfaction, by comparing the quality of service expected from residents and the quality of care received. Results from the adaptation of hosts with a jug of behavior influence and impact on the level of satisfaction.Locations used for research on the Flats are managed by Perum Perumnas (Perusahaan Umum Pembangunan Rumah Nasional) located in the Village 23 Ilir, 24 Ilir, 26 Ilir Bukit Kecil District.This study shows that residents in the Flats Perum Perumnas not satisfied with the quality of care they receive, because there are gaps and level of satisfaction based on dimensions of Tangibles -0.06 and 0.98, Realibility -0.07 and 0.97, Responsive -0.07 and 0.97, Assurance 0.03 and 0.99, Emphaty 0.07 and 0.97 In the analysis of a Cartesian diagram obtained Perumnas statement that residents of the 35 attributes/statement only 11 attributes/statements are satisfied and 6 attributes/ statements that must be addressed.To meet the satisfaction level of residents, managers Flats Perumnas/SP2J need to do a repair of the interior design and installation of water networks.